Speed-flow models for Singapore downtown ring roads - Lim, Elton Chee Yuan (Nanyang Technological University, 2020)
As Singapore continues to tackle the problem of limited land space with a rising population, there is a rising concern about the transport capacities and transport infrastructure to keep up with the expected increase in population. The government has implemented policies such as the Electronic Road Pricing (ERP) system to tackle these issues. For the next generation distance-based pricing ERP system to be implemented effectively in Singapore, a set of current and relevant speed flow models is required. Existing speed-flow models were conducted many years ago and might not well reflect the updated vehicle speed limit and current driver’s behaviour. The main focus of this study is therefore to update the set of speed-flow models for downtown ring roads and to identify the factors affecting the speed-flow curves. Video-recording technique was used to collect traffic speed and traffic volume data from Scotts Road and Balestier Road. Traffic composition analysis and lane width analysis were done to better understand the characteristics of the traffic data collected. Passenger Car Equivalency (PCE) values from previous studies were used to convert the vehicles into equal passenger car units (PCUs). The collected data were fitted into several single and multi-regime speed-flow models and a regression analysis was conducted for individual lanes. After comparing the coefficients of determination (R2) value, the Generalised Drake model was determined to provide the best fit for the data points collected. Comparison between models for Scotts Road and Balestier Road was done and several factors such as number of lanes and lane width were identified to affect the speed-flow model for downtown ring roads. A further study on the speed-flow models for adverse weather conditions was recommended to further account for adjustment factors. The impact of motorcycles on the speed-flow model can also be investigated in further studies due to the tendency of motorcycles to travel in-between lanes.